Decline of Local Democracy: Legal Vacancies, Non-Ideological Coalitions, and the Phenomenon of Single Candidates in Regional Elections in Indonesia - Pratama, Romadhony Putra; Cornelis, Vieta Imelda; Astutik, Sri; Handayati, Nur; Isnawati, Isnawati (Journal of Law, Politic and Humanities, 2026)
The consolidation of democracy in post-Reform Indonesia is currently facing an "illiberal turning point" that systematically erodes the essence of people's sovereignty at the local level through manipulative legal engineering. The urgency of this research is based on the institutional paradox due to the synchronization of the 2024 Simultaneous Regional Elections which triggered mass vacancies and the strengthening of elite hegemony. This study aims to analyze the dialectic of power recentralization through the appointment of Acting Regional Heads, the construction of the doctrine of factual tenure based on the Constitutional Court Decision Number 132/PHPU. BUP-XXIII/2025, as well as the challenges of political cartelization to elite circulation and freedom of choice The main findings of this study show the existence of a "triad of democratic regression" which includes: (1) a crisis of sociological legitimacy due to the appointment of 271 acting regional heads that are centralistic and closed; (2) the establishment of the doctrine of factual tenure as an instrument of substantive justice to prevent the manipulation of tenure by incumbents; and (3) the anomaly of political party cartelization that actually consolidates giant coalitions to create a single candidate even though the nomination threshold has been lowered through the Constitutional Court Decision Number 90/PUU-XXIII/2025. These findings contribute to the understanding that current legal norms tend to be used as instruments of political exclusion to maintain the status quo of the elite. The conclusion of the study confirms that local democracy is undergoing a substantial erosion into just an administrative plebiscite. The implication is that it demands a more strict revision of the Election Law and total transparency in the mechanism for appointing officials. The suggestion for further research is to conduct an empirical evaluation of bureaucratic neutrality under the leadership of the acting and the effectiveness of civil society movements in fighting electoral monopolies.